Effect of two levels of organic matter on some physical properties of tow soil types and tomato productivity under greenhouse system (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2025)
Soil amendments and treatments significantly improve soil structure and enhance crop growth, preventing soil degradation and reduced yields of crops grown in it, and one of them, the addition of manure. A study was conducted by planting tomato plants in plastic columns with a height of 50 cm and a diameter of 25 cm in a greenhouse at Lattakia University campus in 2021 using two types of soil, Loamy soil (L), and sandy Loam soil (SL), and by adding three levels of organic matter (cow manure) 0%, 4% and 8% for each soil, with three replicates. The experiment consisted of 18 columns that were distributed in a completely random design. The effect of these additions on some physical indicators was tracked, and the results showed a decrease that the bulk density of the loamy soil (L) decreased by 0.09 g/cm3 at the 4% addition level and decreased by 0.22 g/cm3 at the 8% addition level. As for the (SL) sandy loam soil, the bulk density decreased by 0.10 g/cm3 at the 4% addition level and 0.20 g/cm3 at an addition level of 8%. The improved bulk density had a positive impact on tomato productivity. The hydrodynamic parameters (a, b) (which are experimental parameters), where the (a) experimental parameter in soil (L) increased from 0.0132 to 0.0862 at the 4% addition level, and to 0.267 at the 8% organic matter addition. This is an increase by 0.253 compared to the control (0.0132). For the SL soil, the parameter (a) increased from 0.118 in the control treatment to 0.489 at the 4% addition level and to 1.035 at the 8% addition level. This constitutes an increase of 0.917 at the 8% addition level compared to the control (0.118).The parameter (b) increased from -7.314 to -5.562 at the level of addition of 8% in the loamy soil (L). An increase by 1.752 in the loamy soil (Al-Hanady soil), while the parameters b increased in the soil (SL) (Al-Hatra) from -5.475 to -4.236 at 8% level of organic matter application, an increased by 1.239 in the sandy loam soil (SL).The results show that the addition of organic matter affected the increase in tomato productivity in the two cultivation media. The increase in the loamy soil (L) by 12.6% and 25 % in the 4 and 8% treatments, respectively, compared to the control. While in the sandy loam soil (SL), productivity was increased by 19.5%and 26.9% in the 4 and 8 % treatments, respectively, compared to the control.